Estudio del valor proteico de la carne de cerdo mediante electroforesis - Arévalo Ledesma, Ambar Valeria (2025)
Globally, pig farming is one of the most important meat industries in agri-food production. In Ecuador, there has been sustained growth in meat consumption, with pork being the second most consumed meat after chicken. Its production is mainly distributed among three farming methods: continuous farming, traditional farming, and free-range farming. However, there are no studies that show variations in the nutritional content, protein content, or molecular profile of the meat according to its origin. The main objective of this research was to determine the protein value of pork using vertical electrophoresis, SDS PAGE method, to obtain a detailed profile of the protein fractions according to their molecular weight (MW). Twelve types of proteins were identified, including heavy myosin, alpha actin, enolase, troponins, and light myosins. This characterization is essential both for scientific research and for industrial applications, as it enables optimization of technological processes, improvement of protein isolate functionality, and assurance of nutritional value. The results were statistically analyzed, revealing significant variations in the percentage of protein present depending on the origin. Meat from traditional farming was found to have the highest protein content, at 23.84%. In contrast, the lowest protein content was recorded in meat from continuous farming operations, with a percentage of 22.89%, suggesting a possible influence of factors such as feed management, rearing conditions, and pre- and post-slaughter stress on protein composition. These results highlight the importance of evaluating not only the type of farming, but also integrated management practices, in order to optimize the nutritional quality of pork.